The determination of unemployment benefits - Rafael DiTella; Robert MacCulloch (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
While much empirical research has been done on the labour market consequences of unemployment benefits, there is remarkably little evidence on the forces determining benefits. The paper presents a simple model where workers desire insurance against the possibility of unemployment and unemployment benefits increase the unemployment rate. We then conduct, what we believe, is one of the first empirical analyses of the determinants of the parameters of the unemployment benefit system. Using OECD data for 1971-1989, controlling for year and country fixed effects, and controlling for the political colour of the government, we find evidence suggesting that benefits fall when the unemployment rate is high. This is consistent with the tax-effect described in Wright (1986) and Atkinson (1990). There is weaker evidence that benefits increase with positive changes in the unemployment rate, which may be proxying for the inflow rate and could be called an insurance effect.
Keywords: H53; J65; 330; endogenous unemployment benefits; unemployment; politics; Arbeitslosenversicherung; Arbeitslosigkeit; Arbeitsmarktpolitik; Zeitpräferenz; Theorie; OECD-Staaten